Location Management Cost Reduction Using Adaptive Velocity-movement Based Scheme - Gembari, M. S.; Habaebi, Habaebi; Noordin, Nor Kamariah; Mohd Ali, Borhanuddin; Prakash, Veeraraghavan (Universiti Putra Malaysia Press, 2005)
Wireless personal communication networks (PCNs) consist of a fixed wireless network and a large number of mobile terminals. These terminals are free to travel within the PC coverage area without service interruption. Each terminal periodically reports its location to the network by a process called location update (or registration). When a call arrives for a particular mobile terminal, the network will determine the exact location of the destination terminal by a process called terminal paging. One major problem that arises in this scenario is the cost associated with paging and registration. Several papers in the literature attempt to reduce the cost by devising new schemes for paging and registration. One of the many interesting schemes was presented by Wan and Lin (1998) that considers a dynamic paging scheme based on the semi-real time velocity information of an individual mobile user, which allows a more accurate prediction of the user location when a call arrives. In this paper, we modified the scheme presented by Wan and Lin by creating an adaptive velocity timer that changes according to the speed of the mobile and applies the same analysis to the movement-based scheme. The investigation shows that the proposed approach of Wan and Lin has better results than what was reported therein and our new approach helps reduce the total cost drastically compared to the original scheme. Results also show that the movement threshold and the adaptive velocity time unit, when they are adaptive, provide significant savings of cost under different cell sizes and velocities in high and low mobility systems.